1993
DOI: 10.1128/mcb.13.12.7334
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic truncation of the first repeat of c-Myb decreases DNA binding in vitro and in vivo.

Abstract: Oncogenic activation of c-Myb in both avian and marine systems often involves N-terminal truncation. In particular, the first of three DNA-binding repeats in c-Myb has been largely deleted during the genesis of the v-myb oncogenes of avian myeloblastosis virus and E26 avian leukemia virus. This finding suggests that the first DNA-binding repeat may have an important role in cell growth control. We demonstrate that truncation of the first DNA-binding repeat of c-Myb is sufficient for myeloid transformation in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 66 publications
6
75
1
Order By: Relevance
“…For example, the N-terminal domain of c-Myb, which v-Myb lacks, was required for activation of the ABCC3 gene, consistent with previous reports suggesting that the N-terminal domain of c-Myb could allow it to interact with additional promoters that are not recognized by v-Myb (Dini and Lipsick, 1993). However, our results showed that the other mutations in v-Myb also affected the activation of specific genes, and that no single mutation was responsible for the dramatic differences observed between v-Myb and c-Myb, suggesting that transcriptional specificity is a complex Figure 6.…”
Section: Discussionsupporting
confidence: 88%
“…For example, the N-terminal domain of c-Myb, which v-Myb lacks, was required for activation of the ABCC3 gene, consistent with previous reports suggesting that the N-terminal domain of c-Myb could allow it to interact with additional promoters that are not recognized by v-Myb (Dini and Lipsick, 1993). However, our results showed that the other mutations in v-Myb also affected the activation of specific genes, and that no single mutation was responsible for the dramatic differences observed between v-Myb and c-Myb, suggesting that transcriptional specificity is a complex Figure 6.…”
Section: Discussionsupporting
confidence: 88%
“…We constructed a set of 17 alanine mutations that targeted (i) residues within the highly conserved DNA-binding domain that had previously been shown to be critical for DNA binding or for transcriptional regulation, (ii) residues within the highly conserved animal-specific C-terminal domain, and (iii) an acidic patch N-terminal to the DNA-binding domain that is present in all closely related Myb proteins of animals and that we have previously shown can regulate DNA binding in vitro and in vivo (5,(22)(23)(24)(25)(26)(27)(28)(29)(30) (Fig. 1).…”
Section: Evolutionarily Guided Alanine Substitution Mutants Of Drosopmentioning
confidence: 99%
“…Rather than targeting patches of highly charged residues that are likely to be exposed on the hydrophilic surface of a properly folded protein, we used multiple protein sequence alignments as a guide for identifying both charged and uncharged regions subject to evolutionarily guided alanine substitution. Our rationale was that because Drosophila Myb is present within the conserved Myb-MuvB or Drosophila Rb E2F and Myb-interacting (dREAM) multiprotein complex, some residues critical for protein function might be required for hydrophobic protein-protein interactions, protein-DNA interactions, or the creation of structural motifs or might be targets for posttranslational modifications (14-16).We constructed a set of 17 alanine mutations that targeted (i) residues within the highly conserved DNA-binding domain that had previously been shown to be critical for DNA binding or for transcriptional regulation, (ii) residues within the highly conserved animal-specific C-terminal domain, and (iii) an acidic patch N-terminal to the DNA-binding domain that is present in all closely related Myb proteins of animals and that we have previously shown can regulate DNA binding in vitro and in vivo (5,(22)(23)(24)(25)(26)(27)(28)(29)(30) (Fig. 1).…”
mentioning
confidence: 99%
“…1A). The loss of R1 and the replacement of the Trp residue probably had only a moderate effect upon the DNA-binding properties of the MYB domain, based on studies carried out in animal R1R2R3 MYB proteins (4,10,11). In contrast, the insertion of the Leu residue in v-MYB, an oncogenic form of c-MYB containing only R2 and R3 (12), completely abolished binding to DNA (13).…”
mentioning
confidence: 99%